Success Factors to Systems Integration Implementation: More Technically Oriented Than Human Related - Abu Bakar, Zaitun (Malaysian Journal of Computer Science, 2001)
This paper is written based on the findings of a survey conducted in the Malaysian public sector IT community. The paper starts with a definition of systems integration and then briefly describes how the study was conducted. This is followed with an explanation of the research questions and a thorough examination on the findings of the survey. The data gathered were used to determine the most critical success factors of systems integration implementation. We conclude the paper by saying that non-technical factors have a stronger influence on the success of systems integration implementation.